The celestial empire path of the dragon (Virginia : Landmark Media Inc., 1994)
This program examines China's relationship with its neighbours and with European nation. It report on how in the 20th century, China's ancient glory gave way to a new form of government, as it finally adapted to the outside worlds.
Part 2 China and the outside world
Copy available in DVD format
Copy available in DVD format
Executive producer, William J. Meabian
Keywords: China -- Social life and customs -- History; China -- Foreign relations -- 20th century